1998
DOI: 10.1046/j.1365-2478.1998.720308.x
|View full text |Cite
|
Sign up to set email alerts
|

Background velocity estimation using non‐linear optimization for reflection tomography and migration misfit

Abstract: We show that it is possible to estimate the background velocity for prestack depth migration in 2D laterally varying media using a non‐linear optimization technique called very fast simulated annealing (VFSA). We use cubic splines in the velocity model parametrization and make use of either successive pairs of shot gathers or several constant‐offset sections as input data for the inversion. A Kirchhoff summation scheme based on first‐arrival traveltimes is used to migrate/model the input data during the veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…While extremely robust, global and semi-global inverse methods have not been widely adopted in traveltime or waveform tomography, although examples do exist (Sen & Stoffa 1991;Varela et al 1998;Sambridge & Mosegaard 2002;Kaufl et al 2013). This is mainly due to the extreme size of the parameter space, and the significant amount of time needed to perform the forward modelling.…”
Section: Global or Semi-global Inverse Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While extremely robust, global and semi-global inverse methods have not been widely adopted in traveltime or waveform tomography, although examples do exist (Sen & Stoffa 1991;Varela et al 1998;Sambridge & Mosegaard 2002;Kaufl et al 2013). This is mainly due to the extreme size of the parameter space, and the significant amount of time needed to perform the forward modelling.…”
Section: Global or Semi-global Inverse Methodsmentioning
confidence: 99%
“…Of specific relevance to this paper is the semi-global method of simulated annealing (Rothman 1985(Rothman , 1986Kirkpatrick et al 1987;Mosegaard & Vestergaarad 1991;Sen & Stoffa 1991;Varela et al 1998). The concepts behind simulated annealing are borrowed from statistical mechanics, specifically from the analysis of a solid cooling in a heat bath.…”
Section: Simulated Annealingmentioning
confidence: 99%
“…For the interpretation of TEM data we utilise very fast simulated annealing (VFSA) as it is more efficient and takes less computing time than other global converging algorithms (SEN and STOFFA, 1995, p. 267). In the VFSA algorithm, the temperature schedule for the acceptance rule is exponentially faster than the one used in conventional simulated annealing (VARELA et al, 1998). An energy (objective) function and governing equations of the process used in the present study are briefly reviewed below.…”
Section: (B) Optimisation Methodsmentioning
confidence: 99%
“…Its use in numerical optimization problems began with Kirkpatrick et al (1983) and its first use in geophysical problems appears to be Rothman (1985Rothman ( , 1986. A review of the method and its application to geophysical problems can be found in Sen and Stoffa (1995) and examples of its use in Sen and Stoffa (1991), Mosegaard and Vestergaard (1991), and Varela et al (1998).…”
Section: Nonlinear Problemsmentioning
confidence: 99%